2021
DOI: 10.5897/err2021.4139
|View full text |Cite
|
Sign up to set email alerts
|

The effect of phenomenon-based learning approach on students metacognitive awareness

Abstract: This study aims to determine the effect of learning activities conducted in accordance with the phenomenon-based learning approach on the metacognitive awareness level of students. Pre-test and post-test control group design of the experimental method was used. The application of the study was carried out in a sample of 60 students studying in the 7th grade of middle school in the 2019-2020 academic year. While "phenomenon-based learning approach" was implemented in the experimental group, traditional teaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Phenomenon-based approaches have been shown to promote improved conceptual understanding and scientific practices such as explanation construction. 3,7,10,21,62 The increased causal mechanistic reasoning we observed after phenomenon-driven instruction provides further evidence that centering learning around observable phenomena facilitates development of explanatory skills. This work contributes insights on using phenomenon-anchored instruction to enhance undergraduates' development of causal mechanistic explanations in chemistry.…”
Section: Causalmentioning
confidence: 64%
See 2 more Smart Citations
“…Phenomenon-based approaches have been shown to promote improved conceptual understanding and scientific practices such as explanation construction. 3,7,10,21,62 The increased causal mechanistic reasoning we observed after phenomenon-driven instruction provides further evidence that centering learning around observable phenomena facilitates development of explanatory skills. This work contributes insights on using phenomenon-anchored instruction to enhance undergraduates' development of causal mechanistic explanations in chemistry.…”
Section: Causalmentioning
confidence: 64%
“…3,6 Coupled with specific ways to reason about chemistry, Phenomenon-Based Learning is a powerful approach to education that can potentially increase student affect and metacognition regarding science content. 7 While Phenomenon-Based Learning originated from K-12 education, some research suggests implementing this approach into college STEM courses. A recent study found that using phenomena can be a strong entry point into online media in response to the COVID-19 pandemic.…”
Section: Students In Science Education?mentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of scientists agree that PhenoBL is directed towards the development of the "4Cs" while investigating certain real-world phenomena from different perspectives (Meriläinen and Piispanen 2012;Symeonidis and Schwarz 2016;Makarova et al 2020;Akkas and Eker 2021). The researchers mentioned here highlight the idea that PhenoBL truly stands for relevant, innovative, substantive, and timely learning.…”
Section: Introductionmentioning
confidence: 81%
“…PhBL also impacts the quality of learning outcomes and overcomes the learning loss phenomenon in elementary schools (Andriani et al, 2023). The results of other studies state that the use of the PhBL model can improve students' learning outcomes (Putri et al, 2018), develop metacognitive thinking skills (Akkas & Eker, 2021), and develop critical thinking skills (Pratiwi et al, 2021). Based on these descriptions, PhBL impacts learning outcomes, overcomes the learning loss phenomenon, and improves students' higher-order thinking skills.…”
Section: Introductionmentioning
confidence: 99%